Terminal Island Sewage Treatment Plant Outfall, Los Angeles Harbor, California: Hydraulic Model Investigation - McAnally, William H. Jr. (U.S. Army Engineer Research and Development Center (ERDC), 1978)
Source: https://erdc-library.erdc.dren.mil/jspui/ Proposed relocations of the Terminal Island Treatment Plant outfall in Los Angeles Harbor were tested in a physical hydraulic model of Los Angeles and Long Beach Harbors, California. The model, with length scales of 1:100 vertically and 1:400 horizontally, reproduced proposed plans of harbor modifications that included dredging and landfill in Los Angeles Harbor and dredging and construction of an oil loading pier in Long Beach Harbor. Five potential locations of the outfall were tested for conditions of a mean tidal range, a modeled effluent representing a prototype effluent of 10 ppt and 76°F discharging into receiving water of 34 ppt and 60°F. The model effluent was dyed red and photographed as it moved through the harbors. Outfall locations along the face of the proposed Los Angeles phase I landfill produced a plume that generally followed an eastward curving path toward the breakwater, passing out through Angel's Gate with ebb phase flows. During flood phase flows some dye moved back northward toward the outfall location. One location, near the western edge of the proposed landfill, showed an instability in direction of plume travel, moving westward at times. Tests of two locations were performed with a possible phase II landfill installed in the model. These tests showed that the outfall location behind the island produced a buildup of dye in that area, whereas a location on the southern (ocean) side of the island permitted dye to readily escape from the harbors via Angel's Gate.